11.48 The misdiagnosis of functional disorders as neurological disease. Issue 12 (14th November 2019) - Walzl, Dennis; Carson, Alan; Stone, Jon
Abstract : Background: When patients with functional neurological disorders are followed up, another neurological disease rarely better explains the initial symptoms in hindsight. No study has examined the reverse, studying patients with various neurological diseases to assess how often a new functional disorder is found which better explains their original symptoms. Methods: We conducted a prospective multi-centre cohort study of 2637 new neurology outpatient referrals from primary care. Neurologists provided initial diagnoses and a rating of the extent to which their symptoms were explained by an 'organic' neurological disease. Patients were followed up 19 months later, via primary care physician questionnaire. Results: Valid responses were obtained for 2378 patients (90% follow up). Ten patients (0.4%) had acquired an unexpected new functional disorder at follow-up which better explained their original symptoms, and 38 patients (1.6%) had acquired an unexpected new 'organic' disease. Conclusion: Patients diagnosed with neurological disease sometimes have a new functional disorder diagnosis at follow-up which better explains the original symptoms. This occurs at a frequency similar to the misdiagnosis of 'organic' neurological disease as functional disorder. Misdiagnosis can harm patients in either direction, which is especially relevant in an era of evidence-based treatment for functional neurological disorders.